Foreign aid: A fillip for development or a fuel for corruption? - Keith Blackburn; Gonzalo F. Forgues-Puccio (Institute for Advanced Development Studies (INESAD), 2011)
We present an analysis of the effects of foreign aid on economic development when the quality of governance may be compromised by corruption. The analysis is based on a dynamic general equilibrium model in which growth is driven by capital accumulation and public policy is administered by government-appointed bureaucrats. Corruption may arise due to the opportunity for bureaucrats to embezzle public funds which are otherwise used to provide productive public goods and services. Our main results may be summarized as follows: (1) corruption impedes economic development and compromises the effectiveness of aid programmers; (2) the incidence of corruption may, itself, be affected by both the development process and the donation of aid; (3) foreign aid is good for development when governance is good, but may be bad (perhaps very bad) for development when governance is bad; and (4) corruption and poverty may co-exist as permanent, rather than just transitory, fixtures of an economy.
Keywords: D73; F35; O11; 330; Corruption; development; foreign aid; Entwicklungshilfe; Entwicklung; Korruption